An Analysis of Soil Moisture Regime in Sal (Shorea robusta) Forests of Dehra Dun, with Reference to Natural Regeneration - Seth, S. K.; Khan, M. A. Waheed (Indian Forester, 1960)
Dehra Dun Valley sal forests, conforming to Champion’s B-3 High Level Alluvium. Type, characteristically reproduce freely but sometimes the reproduction is deficient, particularly in areas which are rigidly fire-protected. The long history of forest management and protection has led to conditions under which large tracts of these forests are not reproducing adequately. The existing conditions have,’ therefore, been investigated with regard to seed-source, seed bed conditions, climate, light, moisture, nutrient requirements and the ameliorative effects of fire. In particular an analysis of the soil moisture regime has been made and correlated with the various developmental stagts of sal seedlings. Suggestions have also been made with regard to adoption of suitable forestry practices to achieve regeneration de novo and to promote the timely establishment of sal seedlings. It is concluded that if the manipulation of sal forests is carried out in a manner conforming to the climato-ecological requirements of sal seedlings, a regeneration period of 15 to 30 years should suffice to restock the area with established sal regeneration.